Peranan Budaya Kerja terhadap Kinerja Pegawai di Dinas Pariwisata Kabupaten Belitung - Tartini Hertin; Amelia Amelia; Yunisti Pratiwi (Yayasan Literasi Sains Indonesia, 2026)
The Indonesian tourism sector has experienced rapid growth, thereby demanding improvements in governance quality and the performance of regional government personnel, including those at the Tourism Office of Belitung Regency. One of the factors estimated to influence employee performance is work culture, particularly the CITRA work culture (Fast, Integrity, Accurate, Friendly, Safe), which serves as a behavioral guideline for government personnel. However, the effectiveness of implementing this work culture within the tourism bureaucracy still requires empirical verification. This study aims to analyze the influence of work culture on employee performance and identify the most dominant aspect of the CITRA values. The research employed a descriptive quantitative method with a saturated sampling technique involving 33 employees. Data were collected through observations and a validated Likert-scale questionnaire. The results indicate that the work culture falls into the good category (78.3%), and employee performance is also categorized as good (71.0%). The correlation value of r = 0.907 (p = 0.000) confirms a very strong relationship between work culture and performance. These findings highlight the strategic role of the CITRA work culture in supporting improvements in public service quality.